Faktor-Faktor yang Memengaruhi Financial Distres di Industri Makanan-Minuman BEI - Syahdina, Aang; Qanitah, Audi Nafisa; Suwandi, Danisha Nazwasabilla; Ramadhan, Eka Gilang; Fhatia, Freethy Libra; Situmorang, Sarah Angelica Puan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The focus of this research is on the impact of liquidity, profitability, and leverage on financial pressures on food and beverage sector manufacturing companies listed on the IDX during the 2020–2023 period. Using a quantitative approach with multiple regression analysis through the Eviews 13 software, this study took 28 corporate samples from 95 populations using the purposive sampling method. The research period covers the Covid-19 pandemic to the beginning of economic recovery. The variables used include Current Ratio (CR) for liquidity, Return on Assets (ROA) for profitability, and Degree of Financial Leverage (DFL) for leverage. The results show that CR and ROA negatively impact financial pressure, while DFL has a positive impact. All three variables simultaneously have a significant effect on financial pressure.